The implications of Trump’s self-defeating 2025 trade war on the global economy - Svetličič, Marjan (Teorija in praksa, 2025)
The biggest problem facing the world economy today is the intensification of neomercantilist policies reinforced by aggressive industrial policies. The USA has declared a trade war on the whole world, and most aggressively on China. The main objective of this article is therefore to find out what the consequences of this trade war for the countries attacked and the US economy are in view of the theory of tariff protection, claiming that in trade wars there are no winners, that all states lose, including the economy of the country that began the war. Among the countries attacked, we are particularly concerned with China and the EU and which policy options they may have available to react to, this trade war. Since this is not the first trade war in history, given that we already had one during the Great Depression in the 1930s, it is necessary to determine whether we have learned from these wars or are merely repeating the mistakes made at that time. It is clear that history has not taught us much. Although this trade war heralds tectonic shifts in the world economy, we conclude that better than reacting in panic is to design a wise, long-term reaction strategy. This is supported by an evaluation of the negotiation profile of the trade war’s initiator, President Trump, characterised by initial dramatizing and blackmailing. The analysis provides arguments concerning why the trade war is not expected to be carried out in such a dramatic way as it was started. All the negative consequences and unrealised objectives for the initiator’s economy will eventually become the basis for the gradual watering down of the most aggressive policy elements.
Keywords: effects; ekonomske krize; Evropska unija; Great Depression; Mednarodna trgovina; Mednarodni gospodarski odnosi; negotiations; pogajanja; povračila; relatiation; tarife; tariffs; trade war; trgovinska vojna; Trump, Donald; učinki; Velika Depresija